PENERAPAN METODE SIMPLE ADDITIVE WEIGHTING UNTUK PENERIMAAN BANTUAN LANGSUNG TUNAI DANA DESA - Hendarman Lubis; Ratna Salkiawati; Sudirman Hala (JSI (Jurnal Sistem Informasi) Universitas Suryadarma, 2022)
The pandemic COVID-19 was entered Indonesia in early 2020 and has impact to economic people. BLT-Dana Desa is a government program to reduce the impact of the pandemic COVID-19. The selection of BLT-Dana Desa recipients still uses the manual method, not mathematically and the number of residents must be selected so that the selection takes longer. The purpose of this study is to design a decision support system in determining the priority of BLT-Village Fund recipients with mathematical calculations so that they can provide priority proposals, speed up the selection process and maximize the level of accuracy of targeting BLT-Village Fund recipients. This determination uses the method Simple Additive Weighting with the criteria of welfare level, age, gender and occupation. This method can make a more precise assessment because it is based on predetermined criteria and preference weights and can rank potential beneficiaries. From the results obtained, Sueb became the main priority for the beneficiary with a preference value of 1, followed by Ucok with a preference value of 0.96 and Udin with a value of 0.8667.Â Keywords: Bantuan Langsung Tunai Dana Desa (BLT-Dana Desa);Â  Simple Additive Weighting (SAW); COVID-19.